Pengaruh Layanan Bimbingan Kelompok Teknik Diskusi Terhadap Pengambilan Keputusan Karir Siswa Kelas XI MAN 2 Kota Semarang - Ikke Ratna Sari; Heri Saptadi Ismanto; Ismah Ismah (Journal on Education, 2024)
There are still many students in class XI MAN 2 Semarang City who still cannot determine the direction of their goals after graduating from school, have not been able to understand themselves, do not know their strengths and weaknesses, do not have an understanding of their future choices and careers, do not have career planning and decide on their career choices. The purpose of this study is to obtain answers whether there is an effect of group guidance services discussion techniques on student career decision making. The type of research used is quantitative research conducted in the form of an actual experimental design with a pre-test and post-test control design. The population of this research is grade 11 students. There are 4 classes with 128 students. The sample selected was XI A which was randomly selected using cluster random sampling technique. The results of the data analysis calculation obtained the average score of the experimental group pre-test results of (96.15%), and the experimental group post-test results of (125.92%). Based on the mean score results, it can be interpreted that after being given counseling services in the discussion technology group, the experimental group's career decision making increased (29.77%). Based on the hypothesis testing analysis, a significant result of 0.000 (two-tailed) was obtained so that 0.000 <0.05. This result explains that Ho is rejected and Ha is accepted by stating, ``There is an Effect of Group Guidance Services Discussion Techniques on Decision Making''.